Integrated Management of Diabetic Peripheral Neuropathy with Naturopathy, Yoga And Diet Control: A Case Report - Singh, Poonam (International Research Journal of Ayurveda & Yoga, 2022)
Today, among metabolic disorders, diabetes can be considered the most common, increasing, serious, and costly public health problem in the World. Among them, microangiopathies leading to nephropathies, optic nerve damage associated with retinopathies, and diabetic peripheral neuropathy (DPN) associated with pain, tingling, or numbness, loss of feeling in the hands, arms, feet, and legs can occur primarily due to uncontrolled diabetes levels. The main reason to visit in a primary care setting is chronic pain. Moreover, it is difficult to treat because of its severity, chronicity, and resistance to simple analgesics. Non-pharmacological approaches and non conventional treatments such as naturopathy, yoga, and diet modification are used to relieve pain, improve well-being, and treat acute, chronic, and degenerative conditions of peripheral neuropathy associated with Type 2 Diabetes Mellitus.